Role of Thin Layer Chromatography in Ascertaining Tikta rasa (bitter taste) of a Medicinal Plant on the Concept of Samana and Vichitrapratyayarabdha Principles of Ayurveda - Mehta, Dr Shital (International Journal of Pharmaceutical & Biological Archive, 2012)
ABSTRACT Ayurveda, the ancient medical science, being accepted by large group of society, stands on its own fundamental principles. Dravyaguna vijnana, which deals with Ayurvedic pharmacology, describes the drug action which is based on Rasadi Panchaka. It describes the classification of a drug (dravya) based on rasa (taste), karma(action) and utpatti(origin), etc. In modern science, as per Bentham & Hooker, classification of a plant is based on its morphological features. Though both the systems of classification are primarily meant for plant classification, no correlation between traditional theory of Rasa panchaka and Bentham & Hooker is reported yet. In present study, two important Tikta rasa (bitter taste) dominant drugs Katuki (rhizome of Picrorrhiza kurroa) and Guduchi (stem of Tinospora cordifolia) falling under samana and vichitra praatyayarabdha category, were subjected to physicochemical parameters and qualitative tests in the context of routine quality control parameters according to API followed by HPTLC study. In light of chromatographic fingerprinting sample preparation protocol is modified to incorporate taste threshold in correlation. Column chromatography is used for first level discrimination technique followed by TLC. Tikta Rasa Dominant Zone (TRDZ) was separated and subjected to TLC fingerprinting. The TRDZ fraction was designated as Botanical Reference Material (BRM) in further analysis. The results show that the planner chromatography technique seems very important and useful when BRM hypothesis was adjunct to method that explains the categorization according to traditional classification method i.e. Rasa domain classification method.